An Algorithm for Strategic Continuation or Restriction of Asthma Medication Prior to Exercise Challenge Testing in Childhood Exercise Induced Bronchoconstriction - Hengeveld, Vera. S.; Keijzer, Pascal B.; Diamant, Zuzana; Thio, Boony J. (Frontiers in Pediatrics, 2022)
Exercise induced bronchial (EIB) constriction is a common and highly specific feature of paediatric asthma and should be diagnosed with an exercise challenge test (ECT). The impact of EIB in asthmatic children’s daily lives is immense, considering the effects on both physical and psychosocial development. Monitoring childhood asthma by ECT’s can provide insight into daily life disease burden and the control of asthma. Current guidelines for bronchoprovocation tests restrict both the use of reliever and maintenance asthma medication before an exercise challenge to prevent false-negative testing, as both have significant acute bronchoprotective properties. However, restricting maintenance medication before an ECT may be less appropiate to evaluate EIB symptoms in daily life when a diagnosis of asthma is well established. Rigorous of maintenance medication before an ECT according to guidelines may lead to overestimation of the real, daily life asthma burden and lead to an inappropiate step-up in therapy. The protection against EIB offered by the combined acute and chronic bronchoprotective effects of maintenance medication can be properly assessed whilst maintaining them. This may aid in achieving the goal of unrestricted participation of children in daily play and sports activities with their peers without escalation of therapy. When considering a step down in medication, a strategic wash-out of maintenance medication before an ECT aids in providing objective support of potential discontinuation of maintenance medication.